Semiotic Analysis of the Representation of Impulsive Buying in the Drama Series “Pay Later” - Baihaqi Ammar Rahadi; Dian Hutami Rahmawati (Lavish Opulent Education, 2025)
This study explores the representation of impulsive buying behavior in the Indonesian drama series Pay Later using a qualitative approach with semiotic analysis. Impulsive buying, often driven by emotional or social triggers, is increasingly normalized in digital consumer culture particularly among young urban populations influenced by media and financial technologies. The purpose of this study is to uncover how visual and narrative elements in the series construct meanings around impulsive consumption. Drawing on Stuart Hall’s theory of representation and John Fiske’s three levels of semiotic analysis reality, representation, and ideology this research examines 18 selected scenes from the series that contain symbolic cues related to consumer behavior. The findings reveal that Pay Later portrays impulsive buying as an emotionally justified and socially accepted behavior, facilitated by seamless financial technology such as Buy Now Pay Later (BNPL) services. Characters are shown using BNPL as a lifestyle solution, often without awareness of long-term consequences. The series also embeds consumerist ideology through status-driven dialogue and dramatized debt consequences such as anxiety, job loss, and family conflict. Additionally, the narrative highlights the influence of social media and self-branding, where impulsive consumption is performed for digital validation. These representations reflect broader socio-economic realities in Indonesia, where financial technology intersects with identity and peer pressure. The study concludes that media texts like Pay Later do not simply reflect consumer behavior but actively participate in shaping it through symbolic and ideological framing. The implication of this research is the need for increased media literacy, particularly in recognizing how media constructs financial norms and consumption values. The findings may be useful for educators, policymakers, and content creators in addressing the impact of media on consumer behavior in the digital era.